2015
DOI: 10.1063/1.4916095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition on magnetocaloric properties of Mn3Ga(1−x)SnxC

Abstract: A study investigating the effect of Sn substitution on the magnetocaloric properties of Mn3Ga (1−x) SnxC compounds reveals that nature of the MCE has a strong dependence on the nature of the magnetic ordering. For small amounts of Sn (x ≤ 0.2) the MCE is of the inverse type wherein an increase in the applied field beyond 5T gives rise to a table like temperature dependence of the entropy due to a coupling between the first order FM -AFM transition and the field induced AFM -FM transition. Replacement of Ga by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…8(a) and 8(b). The maximum value S = 6 ± 0.4 J kg −1 K −1 is in agreement with those obtained for a similar sample from the Maxwell equations [18]. T (T ) calculated using c p (T ) is shown in Fig.…”
Section: In-field Specific Heat and Magnetocaloric Propertiessupporting
confidence: 88%
See 2 more Smart Citations
“…8(a) and 8(b). The maximum value S = 6 ± 0.4 J kg −1 K −1 is in agreement with those obtained for a similar sample from the Maxwell equations [18]. T (T ) calculated using c p (T ) is shown in Fig.…”
Section: In-field Specific Heat and Magnetocaloric Propertiessupporting
confidence: 88%
“…T ad of Mn 3 SnC is only about 0.4 K under 1.8-T field change, however, the virtue of this material is that it exhibits a magnetostructural transition at room temperature, so that if it were to be possible to alleviate AF exchange, the magnetocaloric effect could be enhanced. This could be possible by doping other elements in place of Sn as has been reported in a previous work [18]. The alleviation of AF exchange that could possibly exist in other known materials can be an important task for attaining better magnetocaloric materials.…”
Section: B Implication On Magnetocaloric Effectsmentioning
confidence: 82%
See 1 more Smart Citation
“…A competition between these two interactions can result in both, broad transition and a smaller entropy change. Further, studies on Mn 3 Ga 1−x Sn x C have shown that the strength of antiferromagnetic interactions are critically related to distortions of Mn 6 C octahedra or lattice strain and the effect of lattice strain can be seen in the variation of entropy peak as a function of magnetic field [19]. To check the effect of lattice strain in all the three samples, the change in peak temperature of entropy peak, ∆T = T peak (H) − T peak (0.1T ) is plotted as a function of applied field in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An abrupt decrease in the shorter Mn -Mn distance at T ∼ 175 K results in an AFM ground state and gives rise to a large positive magnetic entropy change (∆S M ∼ 15 J/kg-K at 2 T, equivalent to an adiabatic temperature difference of 3 K) 9,13 . Introduction of Sn for Ga at the A-site results in a lattice expansion as well as a change in the nature of magnetocaloric effect from inverse to the conventional type with ∆S M is about −3 J/kg-K at 2 T applied field 14 . The larger size of Sn also seems to affect the distortions so as to cause the Mn 6 C octahedra to elongate along one direction and shrink along the other two.…”
Section: Introductionmentioning
confidence: 99%